Implementation of design process into engineering education - Titova, Olena; Тітова, Олена Анатоліївна; Титова, Елена Анатольевна (My University, 2018)
Food security of any country as well as economic, environmental and power one relies significantly on agricultural engineering and technologies. In this respect, one of the main strategic objectives for engineering education is to create favourable conditions for training competent experts. As for Ukraine, it is obvious, that Ukrainian agricultural and rural development will require training and employment of highly skilled engineers. So agricultural engineering is not going to lose its value.
Keywords: engineering education; education